Adults with congenital heart disease – Facing morbidities and uncertain early mortality. (March 2018) - Steiner, Jill M.; Kovacs, Adrienne H.
Abstract: In the current era, most individuals born with congenital heart disease will reach adulthood. There are now more adults than children living with congenital heart disease in developed countries, and the population continues to expand. Although the life-saving accomplishments achieved in pediatric cardiology are to be extolled, longer-term sequelae also warrant close attention. Adults with moderate or complex disease continue to face cardiac and noncardiac comorbidities as well as a shorted life expectancy. This article begins with a summary of common comorbidities and patterns of mortality faced by adults with congenital heart disease. This is followed by an overview of the broader impact of these issues on the lives of patients, as well as a call for interdisciplinary and comprehensive care to optimize patient outcomes. Highlights: There are now more adults than children living with congenital heart disease. Cardiac and noncardiac comorbidities are common in adulthood. Most patients are not "cured" and face a shortened life expectancy. The impact of living with congenital heart disease extends beyond medical factors. A comprehensive approach includes psychosocial care and advance care planning.